2019
DOI: 10.1136/bmjopen-2019-030344
|View full text |Cite
|
Sign up to set email alerts
|

Population-based cross-sectional study of 11 645 Spanish nonagenarians with type 2 diabetes mellitus: cardiovascular profile, cardiovascular preventive therapies, achievement goals and sex differences

Abstract: ObjectivesTo evaluate the risk profile, achievement of cardiometabolic goals, and frequency and optimal use of cardiovascular preventive therapies among nonagenarians with type 2 diabetes mellitus (T2DM). To investigate possible sex differences.Design and settingA cross-sectional population study of 11 645 persons aged ≥90 years with T2DM living in Madrid (Spain). Sociodemographic, clinical and therapy profiles were collected through electronic records in primary care. We considered antihypertensive therapy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
1
8
2
Order By: Relevance
“…Our results showed there was no difference in HbA1c between male and female patients with diabetes aged ≥90 years. This is consistent with a previous population‐based cross‐sectional study of 11,645 Spanish type 2 diabetes patients aged ≥90 years, which also showed a similar glycemic control between male and female patients 7 …”
Section: Discussionsupporting
confidence: 93%
“…Our results showed there was no difference in HbA1c between male and female patients with diabetes aged ≥90 years. This is consistent with a previous population‐based cross‐sectional study of 11,645 Spanish type 2 diabetes patients aged ≥90 years, which also showed a similar glycemic control between male and female patients 7 …”
Section: Discussionsupporting
confidence: 93%
“…The literature review identified several studies that reported the prevalence of CVD or a type of CVD in patients with T2DM in special populations, such as those of a predetermined age range or with additional comorbidities (Table 2 ). These studies focused on elderly patients [ 29 , 31 , 35 , 61 ], patients with HF [ 30 , 31 , 33 , 35 ] and patients with kidney disease [ 59 , 60 ]. Several studies reported age as one of the main risks for CVD in patients with T2DM.…”
Section: Resultsmentioning
confidence: 99%
“…Also, a large regional study in Catalonia showed that the prevalence of CVD was 32.3% in patients aged ≥ 75 years and about 10 points lower in the overall population [ 42 ]. Two studies analysed the prevalence of CVD specifically in patients aged 85 and ≥ 90 years, respectively [ 29 , 61 ]: in one study, the prevalence of stroke was slightly higher among patients with T2DM aged 85 years (14.0%) than in studies of the general population [ 29 ]; in the other study, the prevalence of CHD and PAD among nonagenarians with diabetes in the community of Madrid was higher in males than in females (21.5 vs. 12.6% and 8.5 vs. 2.3%, respectively; both p < 0.01) [ 61 ]. However, the prevalence of stroke in the latter study was similar in both sexes (16.5 vs. 16.0%; p = 0.44) [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few years, despite a wide variability in the methodologies and outcome assessments, several studies have shown associations between albuminuria and the risk of developing cognitive impairment and dementia, as well as a correlation with imaging markers for cognitive decline. Moreover, a recent meta-analysis provided the same conclusions [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] based on the results of population-based studies. Less is known about T2D specifically; however, because T2D patients suffer from both an increased risk of cognitive impairment and kidney disease [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ], elucidating the mechanisms of disease and exploring the interplay between the brain and kidney might potentially help to prevent cognitive impairment both in general and T2D populations.…”
Section: Introductionmentioning
confidence: 71%